Blended Problem Based Learning Through SIMPEL-12: Strategies to Improve Economic Critical Thinking Ability - Rizqi Amalia Dwi Asih; Kardoyo Kardoyo; Nina Oktarina (Universitas Negeri Semarang, 2023)
21st Century Learning encourages students to have critical thinking skills, one of which is economics. The problem is, the study of data in the field shows that students lack critical thinking skills in analyzing economic problems. Teachers need to innovate in the application of learning models and media. This study aims to analyze the effectiveness of blended problem-based learning through SIMPEL-12 to improve critical thinking skills. This study uses a quantitative approach with a quasi-experimental design. The results of the hypothesis test showed a significance value of 0.000 <0.05, t hitung (7.268) > t table (1.99444), and the experimental class n-gain test was 0.5258 which was higher than the control class was 0.2732. The conclusion of this research is the blended problem-based learning model through effective SIMPEL-12 to improve the ability to think critically in economics class XI IPS in SMA Negeri 12 Semarang